2019
DOI: 10.1111/ajco.13242
|View full text |Cite
|
Sign up to set email alerts
|

Prior or concurrent radiotherapy and nivolumab immunotherapy in non–small cell lung cancer

Abstract: Background: Studies suggest that combining radiotherapy (RT) with programmed cell death protein 1 (PD-1) blockade may elicit a synergistic antitumor response. We aimed to assess whether prior or concurrent RT was associated with improved disease control in patients with metastatic non-small cell lung cancer (NSCLC) treated with nivolumab. Methods:We conducted a retrospective study of patients receiving nivolumab as second or subsequent line therapy for metastatic NSCLC. Patients were categorized into those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Approximately 2027 patients were enrolled in the 20 studies included in this research. With regard to the study design, nine studies were non-randomized controlled trials (NRCT), [6][7][8][23][24][25][26][27][28] nine were single-arm studies, [29][30][31][32][33][34][35][36][37] and two were RCTs. 5,9 All studies included at least one arm treated with combination therapy using PD-1/PD-L1 inhibitors and RT.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 2027 patients were enrolled in the 20 studies included in this research. With regard to the study design, nine studies were non-randomized controlled trials (NRCT), [6][7][8][23][24][25][26][27][28] nine were single-arm studies, [29][30][31][32][33][34][35][36][37] and two were RCTs. 5,9 All studies included at least one arm treated with combination therapy using PD-1/PD-L1 inhibitors and RT.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…6 Two retrospective studies have shown that combination treatment with RT and nivolumab (a PD-1 inhibitor) in patients with advanced NSCLC may improve OS and PFS without an increase in acute toxicity rates. 7,8 However, a few studies have reported contrasting results. For example, the PEMBRO-RT trial showed that stereotactic body radiotherapy (SBRT) preceding pembrolizumab treatment for metastatic lesions did not improve long-term survival compared with pembrolizumab alone in patients with metastatic NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…These interesting results led to the analysis of further retrospective data in order to find if these benefits could be replicated. In this regard, both Desideri and Ratnayake found similar results in NSCLC patients, with a trend towards a doubling in PFS and OS in those who had received RT and ICI [50,51]. Despite this encouraging data, several new questions arose with respect to timing, dose escalation and other treatment variables.…”
Section: How Did the Preclinical Evidence For The Combination Of Ici And Rt Translate Into The Clinical Setting?mentioning
confidence: 82%
“…In Figure 1 , we can see that sintilimab plus radiotherapy was associated with longer 1-year OS,18-month OS and 2-year OS. A research acted by Theelen W et al ( 15 ), PFS in immunotherapy plus radiotherapy group was notably improved than immunotherapy alone group (p=0.045), and OS was remarkably increased in immunotherapy and radiotherapy group compared with immunotherapy alone group (p=0.0004).A study performed by Gishan et al ( 21 ), there was a significant enhancement in PFS with radiotherapy prior to or concomitant with nivolumab remedy for metastatic NSCLC than nivolumab alone, at the same time, there was no evidence of increased adverse reactions. Additionally, numerous studies show that combining immunotherapy with radiotherapy increases the effectiveness of treatment for NSCLC, with no increase in either radiation or immunological side effects ( 16 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 97%